www.professor.com.br : Experiências do uso da tecnologia na vida profissional e pessoal de professores - Franco, Leticia Bechara Zukovski (2009)
This research investigate the experiences of the teachers in the firsts grades, about the use of the computer as a work tool, trying to identify the relations that teachers are building with the use of technologies in the organizations and planning of the classes, as in the constructions of their pedagogical knowledge that the teachers can do through the use of the computer. In this work is identified the access and the management that the teachers have in every day situation related to the computer (including internet access); and their social representations that they have related to this tool. The process of familiarization was used in the research to show the relation between teachers and computers. Interviews and forms were applied with teachers in both systems: public and private, in São Paulo state, on the first s grades. We also had students from Education College participating of this research. This work showed the level of familiarization of the teachers goes around their interest and individual experience, the professional activities related to the use of the computer. There are no evidences of resistance in the use of the computer; the activities with students go forward in the same steps as the teacher develops himself in the use of the technology.(AU)